Hubungan Antara Status Nutrisi dan Kejadian Sindrom Syok Dengue Pada Pasien DBD Anak - Suriyani Tan; Syahara Aulia Setiawan (Universitas Malahayati Lampung, 2025)
ABSTRACT Dengue Hemorrhagic Fever (DHF) is a disease caused by the Dengue virus and transmitted by the Aedes aegypti mosquito vector. In Indonesia, reported cases in 2022 reached 131,265. Approximately 40% of these cases were in children under five years old, and 70% of the total fatalities occurred in children aged 0-4 years. Nutritional status in young children plays a crucial role in the occurrence of Dengue Shock Syndrome (DSS). The objective of this study is to assess the relationship between nutritional status and the incidence of Dengue Shock Syndrome (DSS) in pediatric patients. This study utilized a cross-sectional design involving 90 pediatric inpatients aged 2-12 years. Data on nutritional status and the incidence of Dengue Shock Syndrome (DSS) were obtained from medical records. Statistical analysis was conducted using the Chi-square test, with the Fisher exact test used as an alternative if the Chi-square test assumptions were not met. The characteristics of the subjects were predominantly children aged 6-12 years and those with overweight nutritional status. A significant relationship was found between nutritional status and the incidence of Dengue Shock Syndrome (DSS) in pediatric patients. It is crucial to conduct nutritional assessments and monitoring as part of the strategy for preventing and managing DHF in children to reduce the risk of DSS. Keywords: Nutritional Status, Dengus Shock Syndrome, Pediatric Patient ABSTRAK Demam Berdarah Dengue (DBD) merupakan penyakit yang oleh virus Dengue dan ditularkan oleh vektor berupa nyamuk Aedes aegpyti. Di Indonesia, kasus yang dilaporkan pada tahun 2022 mencapai 131.265 kasus. Sebanyak 40% kasus diaporkan adalah pada anak balita, dan 70% dari total angka kamatian adalah pada anak usia 0-4 tahun. Status nutrisi pada anak balita memegang peranan penting pada kejadian Sindrom Syok Dengue (SSD). Tujuan dari studi ini adalah untuk menilai hubungan antara status nutrisi dengan kejadian SSD pada pasien anak. Studi ini menggunakan desain potong lintang pada 9pasien anak yang berusia 2-12 tahun yang menjalani rawat inap. Data status nutrisi dan kejadian SSD diambil dari data rekam medis. Analisa statistik dilakukan dengan uji Chi-square dengan uji Fischer exact sebagai pengganti uji pengganti jikalau uji Chi-square tidak memenuhi syarat. Karakterikstik subjek didominasi oleh anak yang berusia 6-12 tahun dan status gizi lebih. Terdapat hubungan yang bermakna antara status nutrisi dengan kejadian SSD pada pasien anak. Sangat penting untuk melakukan penilaian dan pemantauan status nutrisi sebagai bagian dari strategi pencegahan dan penanganan DBD pada anak untuk mengurangi risiko terjadinya SSD. Kata Kunci: Status Nustrisi, Sindrom Syok Dengue, Pasien Anak